2011
DOI: 10.1108/s0198-8719(2011)0000022011
|View full text |Cite
|
Sign up to set email alerts
|

The Tea Party in the Age of Obama: Mainstream Conservatism or Out-Group Anxiety?

Abstract: With its preference for small government and fiscal responsibility, the Tea Party movement claims to be conservative. Yet, their tactics and rhetoric belie this claim. The shrill attacks against blacks, illegal immigrants, and gay rights are all consistent with conservatism, but suggesting that the president is a socialist bent on ruining the country, is beyond politics. This paper shows that Richard Hofstadter's thesis about the "paranoid style" of American politics helps characterize the Tea Party's pseudo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 23 publications
0
42
0
1
Order By: Relevance
“…Some authors have noticed that this profile is consistent with that of the rightwing populist electorate (Sunstein & Vermeule 2009;Barreto et al 2011). In this respect, it is possible to argue that populist rhetoric has something to share with conspiracist ideation.…”
Section: Determinants Of Conspiracism: a Set Of Hypothesesmentioning
confidence: 57%
See 1 more Smart Citation
“…Some authors have noticed that this profile is consistent with that of the rightwing populist electorate (Sunstein & Vermeule 2009;Barreto et al 2011). In this respect, it is possible to argue that populist rhetoric has something to share with conspiracist ideation.…”
Section: Determinants Of Conspiracism: a Set Of Hypothesesmentioning
confidence: 57%
“…Nonetheless, several studies employing small samples and experimental designs found a relationship between political views and beliefs in general conspiracies, arguing that general conspiracism is mainly a populist, rightwing phenomenon (Sunstein & Vermeule 2009;Barreto et al 2011). Other studies found no connection whatsoever between partisanship and this type of conspiracism (Oliver & Wood 2014).…”
Section: Determinants Of Conspiracism: a Set Of Hypothesesmentioning
confidence: 99%
“…This research claims that Tea Party members are more racially conservative than non-Tea Party supporters (Abramowitz 2011 ;Barreto et al 2011 ;Parker 2010 ;Parker and Barreto 2013 ); however, the evidence is mixed (Arcenaux and Nicholson 2012 ; Foley 2012 ).…”
Section: Background On the Tea Party Movementmentioning
confidence: 94%
“…The Occupy movements of 2011–2012 were successful in mobilizing action for a short time because of an intuitive diagnosis (“Wall Street” as a symbol of evil finance and the culprit for the latest financial crisis), prognosis, and motivation, by specifying a concrete course of action (“occupy”), and by a claim of salience and credibility relevant to many constituencies of the public, which connected the action to deeply held values of democracy and fairness (“We are the 99 percent”). At the other end of the political spectrum, the right-wing US Tea Party attracts anxiety-driven adherents of CTs about government (Barreto et al, 2011). …”
Section: Explaining How Cts Mobilize Collective Action: Frame Theorymentioning
confidence: 99%